Power-delay product minimization in high-performance 64-bit carry-select adders. - Neve, A. (IEEE Transactions on VLSI systems)
This paper analyzes methods to minimize the power-delay product of 64-bit carry-select adders intended for high-performance and low-power applications. A first realization in 0.18-μm partially depleted (PD) silicon-on-insulator (SOI), using complex branch-based logic (BBL) cells, results in a delay of 720 ps and a power dissipation of 96 mW at 1.5 V. The reduction of the stack height in the critical path, combined with the optimization of the global carry network with cell sharing and the selection of 8-bit pre-sums, leads to a reduction of the power-delay product by 75%. The automatic tuning of the transistor widths in 0.13-μm PD SOI produces an energy-efficient 64-bit adder which has a delay of 326 ps and a power dissipation of 23 mW only at 1.1 V.